(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2023)
Co-teaching has been a practice for a while to promote collaboration among teachers who are faced with an increasingly diverse classroom environment in terms of students linguistic, sociocultural and economic backgrounds and learning differences. It has become a common practice and researched topic between content and inclusive teachers to promote best practices in inclusive classrooms (MACHATON; DANIEL, 2008; MOFIELD, 2019; HEISLER; THOUSAND, 2019; ALNASSER, 2021; DIEKER; MURAWSKI, 2023). It has also been researched as pre-service and in-service practices in various school contexts (PARK, 2014; PRATT, 2014; ALTSTAEDTER; SMITH; FOGARTY, 2016; WEINBERG et al, 2020). In Brazil, some studies show that collaboration and co-teaching have been researched practices in practicums and in programs like Programa Residência Pedagógica (PRP) and Programa Institucional de Iniciação à Docência (PIBID) sponsored by CAPES (PEREIRA, 2013; SOUZA; 2016; FARIAS; 2020). We would like to reflect how this conversation sheds light on the teaching of English in the context of the public school system in Bagé where PRP - Núcleo de Língua Inglesa, a program sponsored by the Universidade Federal do Pampa (Unipampa). We call PRP - Núcleo de Língua Inglesa English Residency and the student-teachers, residents while the public school teachers are called leading teachers. The complexities of teaching require extensive experience in the classroom in order to foster an understanding of the learners and of the environment of both the classroom and the school (GU, 2018). Co-teaching is a way to help teachers better understand and navigate those complexities as they feel less isolated, gain autonomy, and learn to collaborate. The outcomes can be more effective teaching as they bridge theory and practice as co-teaching can range from collaborative planning, teaching (delivering instruction), and assessing to sharing a physical space and responsibilities for one or more groups of students (WEINBERG et al, 2020). Following co-teaching research patterns, this study sponsors a qualitative approach (SUASSUNA, 2008) as sponsored by Grupo de Pesquisa Diálogos do Pampa (PARZIANELLO, 2020). The instruments used are class observations, individual semi-structured interviews, and group interviews. Finding out the residents’ perceived benefits or impacts and the challenges of their co-teaching experiences and affordances (the pedagogical properties of the co-teaching environment that enable residents to learn how to teach English) is the goal of this study. We categorize the responses following the way co-teaching happens and also how it is perceived. In our context, co-teaching can happen among two residents and a leading teacher or between a resident and a leading teacher. Leading teachers are always accompanying the residents and sometimes helping them out in the classroom. In some cases leading teachers offer help in the face of trouble to achieve instructional goals and keep students engaged in the lessons. There are sixteen residents and three leading teachers. In this context, co-teaching happens part-time or intermittently; that is, residents generally teach once a week two, three or four classes depending on the public school for the duration of the school year. They use diverse co-teaching strategies (one teach-one observe; one teach-one assist; station teaching; parallel teaching; supplemental teaching; alternative teaching; team teaching). Our reflections reveal differing participant perceptions of the co-teaching experience. Some residents sponsor the concept of achieving symbiosis (PRATT, 2014), which means that they became effective in their collaboration through using personal differences and strengths to become interdependent and to create engaging lessons and teaching experiences. Other residents show that collaboration is not necessarily planned but rather occurs to meet unforeseen interactional and instructional needs, especially between residents and leading teachers. Others show that collaboration needs to be explicitly taught in terms of strategies in order to be accomplished. Similar to the research conducted by Alnasser (2021), they show lack of a shared understanding of co-teaching and lack of co-teaching planning time. Our research shows that the presence of two co-residents may help them teach and learn how to teach in a more critical, reflexive, and comforting environment. In order for that to happen, however, effective instructional supervision, a set of clear expectations, and opportunities for individual and group reflection should be provided. It is our understanding that co-teaching experiences can provide opportunities to English residents to develop their knowledge about teaching and learning English while becoming more autonomous collaborative teachers. We thank CAPES for the scholarship for the members of Núcleo de Língua Inglesa (PRP) and also the methodology meetings with Grupo de Pesquisa Diálogos do Pampa (CNPq).